Eyes of Optimism Look for Freedom in Langston Hughes' Selected Poems (Journal of the College of Languages (JCL), 2016)
The current study tackles how slavery and racial segregation, which have obviously made an enormous impact in the United States of America for many years, can be defeated through optimism. The study opens with an introduction that clarifies some background about Langston Hughes as a poet who writes against slavery and oppression done to the American Blacks during an era which was known for racial segregation in the United States of America. The poet sheds light , in his poetry, upon the role of African Americans in activating hope and optimism to get freedom which has been reached at the end. The first section of the study analyzes the meaning of slavery and segregation as reflected in some selected poems, showing the oppressive face of the Whites against the Blacks. The poems exhibit simplicity as the poet's main strategy to raise one of the most sensitive cases in history; that is slavery. The second section comes next where the poet works on instigating his people towards the necessity of keeping on optimism as the key that will lead to man's freedom . Finally , the conclusion that sums up Hughes' message of how African Americans must convey the optimistic view throughout the African American history for eternal freedom. African Americans have suffered from racial discrimination for years as they have been used as slaves. They also have to face an inner migration from the South of America where they are used as workers in the farms which belong to the White owners , and to some blacks who managed to have prosperity at the expense of the poor Blacks. Poverty has dominated their life and most of them have become jobless , in addition to being uneducated. The poet writes his poems in time that literature , in general, and poetry , in particular, represent the spring from which the Blacks start their revolution against racism. He presents the African spirit of their ancestors who are known for their struggle and strife making their cause extend to include the next generations. Optimism and hope can be seen in these old spirits as a motivation for the present and the future as well. Hughes depends on some images that are taken from the Blacks' history with other images are seen in the present in order to build the future that the Blacks themselves look for ; the future of having freedom and equality. Being desperate is something dangerous and cannot lead to build up an optimistic generation in the African-American community. The poet's message is to run after the eye which looks at the optimistic spirit which put the reader in the position of evaluating the African-American history that celebrates the human strife in the past and the present by reminding his people of hope and optimism as the main source for their battle against racial discrimination.